Fishing Into the MicroRNA Transcriptome - Herkenhoff, Marcos E. [UNESP] (2018)
In the last decade, several studies have been focused on revealing the microRNA (miRNA) repertoire and determining their functions in farm animals such as poultry, pigs, cattle, and fish. These small non-protein coding RNA molecules (18-25 nucleotides) are capable of controlling gene expression by binding to messenger RNA (mRNA) targets, thus interfering in the final protein output. MiRNAs have been recognized as the main regulators of biological features of economic interest, including body growth, muscle development, fat deposition, and immunology, among other highly valuable traits, in aquatic livestock. Currently, the miRNA repertoire of some farmed fish species has been identified and characterized, bringing insights about miRNA functions and novel perspectives for improving health and productivity. In this review, we summarize the current advances in miRNA research by examining available data on Neotropical and other key species exploited by fisheries and in aquaculture worldwide and discuss how future studies on Neotropical fish could benefit from this knowledge. We also make a horizontal comparison of major results and discuss forefront strategies for miRNA manipulation in aquaculture focusing on forward-looking ideas for forthcoming research.